Ecological empowerment and Enterprise Zones: pain free transitions to sustainable production in cities or fool's gold?. (15th October 2016) - Monaghan, Philip; North, Peter; Southern, Alan
Abstract: An Enterprise Zone (EZ) based on cleaner production is an increasingly popular government policy to accelerate the sustainable cities agenda. The purpose of this review paper is to critique EZ theory and the credibility of policy transfer to sustainable production in cities. To this end we undertook a literature review on EZ theory; produced a survey of cleaner production EZs to highlight its application in England; and developed a conceptual framework for a triple bottom line form of EZ. Based on our findings we argue that for the credible transfer of EZ theory to the sustainable cities agenda, policy should align to our conceptual framework for an Ecological Empowerment and Enterprise Zone (EEEZ). The EEEZ is an EZ which is ecologically restorative, places an emphasis on community involvement to better harness market forces, and understands the utility of state with the public sector as an entrepreneur. These research results will be of value to the literature focused on spatial low carbon enterprise strategy. Highlights: Our survey results suggest that cleaner production EZs are a common phenomenon in England four fifths of the 24 EZs in operation have an explicit interest. Examples include Sunderland's low carbon vehicle corridor and Hull's green port with offshore energy. However, our typology to analyse EZs also indicates they display different sustainable characteristics.